Cultural Resistance Through Bri’s Rap In Angie Thomas On The Come Up - Yohanes Donbosco Wogo Lusi; Putut Handoko; Kusuma Wijaya (PT. Padang Tekno Corp, 2025)
This study examines cultural resistance through Bri’s rap in On the Come Up by Angie Thomas. Using Stephen Duncombe’s framework, this qualitative research explores how Bri’s rap serves as a free space for self-expression, a tool for challenging oppression, and a catalyst for political awareness. The findings indicate that Bri’s rap creates free spaces where marginalized voices can reclaim agency, reject stereotypes, and resist systemic control, and a stepping stone to political action. Additionally, her lyrics highlight racial profiling, media misrepresentation, and the exploitation of Black artists, reinforcing rap’s role as a medium of activism. Ultimately, this study concludes that Bri’s rap is not just a form of entertainment but a means of identity negotiation, empowerment, and collective resistance.